MEDIA AND PROMOTIONAL CAMPAIGNS OF THE ORGANIZATION FOR THE PROTECTION OF ANIMAL RIGHTS "PETA" - Grubor, Tatjana (Napredak, 2021)
This paper deals with the issue of the relationship between humans and animals in the past from prehistory to the present day,with special emphasis on the ideas, goals and achievements of the organization for the protection of animal rights PETA (People for the Ethical Treatment of Animals). As people themselves do not problematize their behavior towards animals, there are organizations that try to point out the biggest problems of inhumane treatment of animals in research laboratories, farms, the entertainment industry, but also the behavior of each individual. Animal protection societies operate in two ways, fighting large industries globally, forcing positive laws, lobbying national governments and international alliances and organizations, but also at the level of each person, trying to take small steps to develop awareness of the need to care for animals and change attitude towards them. The world's largest organization for the protection of animal rights, PETA, is leading in that fight with its activities and campaigns. Using all means, often on the verge of scandal, he grabs as much of the media space as possible, and with the development of modern social networks, it finally has daily access to a huge number of interested people around the planet.
Keywords: Peta; animal rights; environmental campaigns; ecoterrorism; media campaigns